(untitled) (CIPEEX, 2025)
The principle of procedural good faith is fundamental to guaranteeing reliability and justice in the legal system, and is associated with the honesty and loyalty of the parties during the judicial process. Given this context, the following question arises: has the principle of good faith been properly implemented by the Brazilian legal system? Given the importance of the principle of good faith for the integrity and fairness of legal relations, the question arises as to whether this principle has been effectively implemented in the Brazilian legal system. The general objective of this project is to analyze whether the principle of good faith has been implemented in the Brazilian legal system. As for the specific objectives, the aim is to discuss the doctrinal concept of the principle of procedural good faith, address the legal provision of this principle in the Brazilian legal system and analyze the effective implementation of good faith in the national legal context. The methodology adopted in this study will consist of carrying out a bibliographical review on the doctrinal concept of the principle of good faith, using the author Professor Humberto Teodoro Junior (2021) as a reference, and also analyzing the legal provisions that provide for this principle, especially art. 278 of the CPC and other provisions of the Federal Constitution related to the subject. In addition, the Jornal Jurídico website will be consulted, specifically the news item "Nulidades de algibeira: a estratégia rejeitada pela jurisprudência em defesa da boa-fé procedural", to support the analysis of the implementation of the principle of good faith in Brazilian legal practice. This project is justified by the importance of evaluating the effectiveness of the principle of good faith in the Brazilian legal system, considering its crucial role in promoting ethics, transparency and justice in legal relations. Furthermore, the scientific analysis of this principle contributes to the advancement of legal knowledge and the ethical evolution of society. It is hoped that this study will provide a contextualized assessment of the implementation of the principle of good faith in the Brazilian legal system, considering both its legal provision and its practical application. The analysis of the results will make it possible to identify the strengths and weaknesses in the implementation of this principle, contributing to the improvement of the legal system and the promotion of equitable justice.